Probability Factors Affecting Income Smoothing in Banks in 2010−2016 - Kartika Dewi (Bina Nusantara University, 2018)
The purpose of this research was to examine profitability factors in banking that affected income smoothing. Profit is the most important number for readers in making the economic decision. This research used probability factors that affected income smoothing in the bank. Probability ratio testing used Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expense Ratio (OER). The population was all banks listed in Indonesian Stock Exchange in 2010-2016. The sample was 203 data obtained through purposive judgment sampling. Using Logistic Binary Regression from SPSS version 20, Eckel Index was used to determine which companies smooth its income. The result shows that ROA, NIM, and OER are significant to income smoothing. However, ROE does not affect income smoothing significantly.